Antisynthetase Syndrome-Associated Interstitial Lung Disease: Monitoring of Immunosuppressive Treatment Effects by Chest Computed Tomography - Korsten, Peter; Rademacher, Jan-Gerd; Riedel, Linn; Schnitzler, Eva-Maria; Olgemöller, Ulrike; Seitz, Cornelia Sabine; Schmidt, Jens; Larsen, Jörg; Vasko, Radovan (Frontiers in Medicine, 2021)
Background Antisynthetase syndrome (ASyS) is a rare autoimmune disease characterized by inflammatory myopathy, arthritis, fever, and interstitial lung disease (ILD). Pulmonary involvement in ASyS significantly increases morbidity and mortality and, therefore, requires prompt and effective immunosuppressive treatment. Owing to the rarity of ASyS, limited data exists on progression and prognosis of ILD under immunosuppression. Objectives The objective of the study was to evaluate the radiological progression and outcome measures of ILD with immunosuppressive therapy in patients with ASyS. Methods Twelve patients with ASyS-associated ILD (ASyS-ILD) were included. Demographic and clinical data, including organ involvement, pulmonary function tests, laboratory parameters, imaging studies and treatment regimens were retrospectively analyzed from routinely collected data. The extent of ground glass opacities, fibrotic changes and honeycombing was analyzed and scored using high-resolution chest computed tomography (HRCT) scans. HRCT findings were compared between baseline and follow-up examinations. In addition, patients were stratified depending on whether they had received rituximab (RTX) or not. Results Pulmonary function tests revealed stable lung function and follow-up HRCT scans showed an improvement of radiological alterations in the majority of ASyS patients under immunosuppressive therapy. We did not detect significant differences between the RTX- and non-RTX-treated groups, but the RTX-treated patients more frequently had myositis and relapsing disease. Conclusions Radiographic alterations in ASyS-associated ILD respond to immunosuppressive treatment. RTX is a feasible treatment option with similar clinical and radiographic outcomes in patients with relapsing disease and clinically apparent myositis.